Learning to see after early and extended blindness: A scoping review - May, Eloise; Arach, Proscovia; Kishiki, Elizabeth; Geneau, Robert; Maehara, Goro; Sukhai, Mahadeo; Hamm, Lisa M. (Frontiers in Psychology, 2022)
Purpose: If an individual has been blind since birth due to a treatable eye condition, ocular treatment is urgent. Even a brief period of visual deprivation can alter the development of the visual system. The goal of our structured scoping review was to understand how we might better support children with delayed access to ocular treatment for blinding conditions. Method: We searched MEDLINE, Embase and Global Health for peer-reviewed publications that described the impact of early (within the first year) and extended (lasting at least 2 years) bilateral visual deprivation. Results: Of 551 reports independently screened by two authors, 42 studies met our inclusion criteria. Synthesizing extracted data revealed several trends. The data suggests persistent deficits in visual acuity, contrast sensitivity, global motion, and visual-motor integration, and suspected concerns for understanding complex objects and faces. There is evidence for resilience in colour perception, understanding of simple shapes, discriminating between a face and non-face, and the perception of biological motion. There is currently insufficient data about specific (re)habilitation strategies to update low vision services, but there are several insights to guide future research in this domain. Conclusion: This summary will help guide the research and services provision to help children learn to see after early and extended blindness.